1973
DOI: 10.3758/bf03326949
|View full text |Cite
|
Sign up to set email alerts
|

An age related position reversal impairment in the rat

Abstract: Seventeen-day-old and 38-day-old rats were compared on position habit reversal. 5s were drawn from the same litters and assigned randomly to either the 17-daY- Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1974
1974
1987
1987

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The unsystematic pattern of goal-arm selections among 15-day-olds suggests that ontongenetic variation in the utilization of stimuli may underlie developmental shifts in spontaneous alternation, Altman, Brunner, and Bayer (1973) have suggested that the 2-or 3-week-old domestic rat is behaviorally similar to the hippocampectornized adult of the species. Further, maturation rates of cells at the dentate gyrus and the development of cholinergic control over behavior are consistent with this brain-development hypothesis (Campbell, Lytle, & Fibiger, 1969;Douglas, 1972).This particular behavioral syndrome, typical of the young rat, includes: (a) elevated and persistent motor activity (Bronstein, Neiman, Wolkoff, & Levine, 1974;Campbell et al, 1969;Feigley, Parsons, Hamilton, & Spear, 1972), (b) considerable difficulty in the acquisition of a passive-avoidance task to a footshock US (e.g., Ricco & Marazzo, 1972), (c) impaired position-habit reversal (Harley & Moody, 1973), and (d) low levels of spontaneous alternation (Douglas, Peterson, & Douglas, 1973;Kirkby, 1967). The present paper describes attempts to replicate and to further understand the age-related differences in spontaneous alternation.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…The unsystematic pattern of goal-arm selections among 15-day-olds suggests that ontongenetic variation in the utilization of stimuli may underlie developmental shifts in spontaneous alternation, Altman, Brunner, and Bayer (1973) have suggested that the 2-or 3-week-old domestic rat is behaviorally similar to the hippocampectornized adult of the species. Further, maturation rates of cells at the dentate gyrus and the development of cholinergic control over behavior are consistent with this brain-development hypothesis (Campbell, Lytle, & Fibiger, 1969;Douglas, 1972).This particular behavioral syndrome, typical of the young rat, includes: (a) elevated and persistent motor activity (Bronstein, Neiman, Wolkoff, & Levine, 1974;Campbell et al, 1969;Feigley, Parsons, Hamilton, & Spear, 1972), (b) considerable difficulty in the acquisition of a passive-avoidance task to a footshock US (e.g., Ricco & Marazzo, 1972), (c) impaired position-habit reversal (Harley & Moody, 1973), and (d) low levels of spontaneous alternation (Douglas, Peterson, & Douglas, 1973;Kirkby, 1967). The present paper describes attempts to replicate and to further understand the age-related differences in spontaneous alternation.…”
mentioning
confidence: 57%
“…This particular behavioral syndrome, typical of the young rat, includes: (a) elevated and persistent motor activity (Bronstein, Neiman, Wolkoff, & Levine, 1974;Campbell et al, 1969;Feigley, Parsons, Hamilton, & Spear, 1972), (b) considerable difficulty in the acquisition of a passive-avoidance task to a footshock US (e.g., Ricco & Marazzo, 1972), (c) impaired position-habit reversal (Harley & Moody, 1973), and (d) low levels of spontaneous alternation (Douglas, Peterson, & Douglas, 1973;Kirkby, 1967). The present paper describes attempts to replicate and to further understand the age-related differences in spontaneous alternation.…”
mentioning
confidence: 99%
“…The young of most altricial species are thought to pass through periods of development in which they are more active and impulsive than their more quiescent adult counterparts. Play and exploratory behavior are generally more prevalent in young than in older animals (Welker, 1971), and by several criteria young animals have difficulty withholding active responses (Riccio & Marazzo, 1972;Riceio, Rohrbaugh, & Hodges, 1968) or in shifting from one response set to another (Harley & Moody, 1973;Kirkby, 1967). Furthermore, a number of studies have demonstrated that young animals are slow or even fail to habituate both to phasic stimulation and to more general environmental changes (Bronstein, Neiman, Wolkoff, & Levine, 1974;Feigley, Parsons, Hamilton, & Spear, 1972).…”
mentioning
confidence: 99%